Schtetl, schund, rebellion and Palestine - Radziszewska, Krystyna; Dekiert, Dariusz; Wiatr, Ewa (Wydawnictwo Uniwersytetu Łódzkiego, 2025)
Texts presented in this anthology exemplify the phenomena occurring in the Jewish literature in Łódź at the turn of 20th century. They form a reflection of social and cultural changes, trends, fascinations and fears typical of a young Jewish generation living in a modern industrial metropolis. Its time frame is defined by the turn of century for two religions: the beginning is marked by 1905, a highly significant year in Łódź history, and the turn of the 20th century in the Gregorian calendar. The end is marked by 1 Tishri 5700 (14 September 1939), which is the beginning of a new century in the Hebrew calendar. The time between the Revolution of 1905 and the Shoah was a period of intensive developments in Jewish literature as well as in social life. It manifested itself through hundreds of publications, newspapers and numerous transient literary magazines – locally called “ephemerals” – each of which had an edition of only a handful of copies. A selection from a wealth of sources belonging to a different religious and cultural environment, published in various languages, was based on a specific categorization. A standard classification might not be adequate: it would carry the risk of misrepresenting the original message through the use of concepts and categories which, though present in Jewish culture and history, often failed to convey the same meaning. The adopted criteria for the choice and grouping of texts are based on four Jewish concepts, which facilitates the understanding of the cultural phenomenon of Jewish community in Łódź at the time.